Supply Chain Strategy and Human Resource Competency: The Foundation of Manufacturing Company's Excellent Performance - Okin Ringan Purba; Edi Abdurachman; Edhie Budi Setiawan; Nofrisel Nofrisel (Dinasti Publisher, 2024)
In Indonesia, the development of the manufacturing industry is considered rapid due to the swift logistics process from producers to consumers. This is related to how and when a product is delivered, making it equally important as the product itself. The progress of the manufacturing industry in Indonesia is also influenced by the advancement of technology, which continuously improves and evolves the Supply Chain process. This research is conducted with the aim of analyzing Supply Chain strategies and human resource competencies as antecedents to the competitive advantage of manufacturing companies. The research was conducted using a quantitative method approach and involved 4 variable constructs consisting of Supply Chain Strategy, Human Resource Competencies, Competitive Advantage, and Company Performance. These five variable constructs are measured with 42 valid and reliable measurable indicators using a questionnaire and a Likert scale of 1-5. The questionnaire was distributed to manufacturing company managers in the DKI Jakarta Province from November to December 2023, using stratified sampling techniques with a total sample of 323 respondents. The data was processed using SEMPLS software. The results of 7 hypothesis tests depict that there is a positive and significant influence of Supply Chain Strategy on company performance; Supply Chain Strategy, Human Resource Competencies, and Competitive Advantage, as well as Human Resource Competencies on Competitive Advantage; Supply Chain Strategy, Supply Chain Strategy, and Human Resource Competencies significantly influence company performance through Competitive Advantage. It is concluded that both directly and indirectly there is a significant influence of Supply Chain strategy and human resource competencies as antecedents to the competitive advantage of manufacturing companies.